ANALISIS PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PEMBERIAN PELAYANAN PUBLIK (STUDI PADA KELURAHAN CAKUNG BARAT KECAMATAN CAKUNG KOTA JAKARTA TIMUR) - Prameswari, Rosita; Susetyo, Ivan Budi (Jurnal Ilmu Administrasi Publik, 2025)
This research discusses the implementation of good governance principles in public service delivery at Cakung Barat Sub-District, East Jakarta. The objective of the research is to analyze how principles such as accountability, transparency, openness, and the rule of law are applied in the sub-district. The research employs a descriptive qualitative approach involving in-depth interviews and Nvivo data processing. The findings indicate that good governance principles have been well implemented, particularly in terms of accountability and openness, through effective communication and the availability of suggestion boxes. However, several challenges were identified, such as delays in service delivery and limited human resources. This research also highlights the importance of enhancing public service quality through human resource training and the optimization of information technology usage. This research provides valuable insights for local governments to improve service quality based on good governance principles, particularly in creating efficient, fair, and transparent services for the  community.